A eficácia do planejamento na construção civil : análise dos indicadores de custo, prazo e ritmo - Talita de Souza Oliveira (2021)
The production planning and control process is expanding since it generates benefits that enable the increase in performance of construction projects, in relation to cost, term, quality and safety. Therefore, many construction companies have placed greater importance on the development and implementation of performance measurement systems. These systems contribute to that the main focus of activities, be in results, requiring a set of indicators related to the company's strategies, action plans and goals. The present study had as main objective to refine the indicators that intend to quantify the efficiency of planning in civil construction. For that, were used Indicators of Deviations of Cost, Term and Pace and sought to establish relationships between short and long term planning. Four works were evaluated in the state of Minas Gerais, carrying out a series of statistical analyzes in the complete work and in partial periods, allowing the visualization of the indicators during its evolution. Statistical analyzes were performed, considering three types of studies: searching to observe a relationship between indicators, were performed correlation tests; in order to find the equation that best explains a relationship between variables, regression analyzes were performed; and in order to characterize the stages according to the indicators, the descriptive statistical analysis was performed. In general, as the work progressed the average of the indicators improved, so the stage corresponding to the total construction presented better results in the descriptive analysis. For correlation analyzes, the best relationship observed was between the Deviations of Term and Rhythm in the stages of 60% and 80%. This result is expected since the higher the pace, the better the term. Through the regression analysis it was possible to determine the best type of equation to establish the relationship between the indicators, and the cubic equation was the one that presented the best results. It is hoped that this study can contribute to the advancement of knowledge about the relationships between the indicators that also evaluate the performance of the construction, reinforcing the importance of production planning and control in civil construction.